PENGARUH CAR, NPF, BOPO, FDR, TERHADAP ROA YANG DIMEDIASI OLEH NOM - Muhammad Yusuf Wibisono; Salamah Wahyuni (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
This study aims to analyze the influence of Net Operating Margin (NOM) as mediation between Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational Cost compared to Operating Income (BOPO), and Financing Debt to Ratio (FDR) to Return On Assets (ROA). The research data is pooling data that is combination between time series and cross section during the period of 2012 until 2015, so get the observation number (point of observation) as 9 syariah bank listed in BEI.The results of the research are CAR, NPF, BOPO, FDR, and NOM variables affecting ROA partially. CAR and NPF variables have no significant effect on ROA, while the FDR, BOPO variable has a significant negative effect on ROA, and NOM has positive positive effect on ROA. The NOM variable mediates the effect between CAR, NPF, BOPO and FDR against ROA. Key Words : NOM, CAR, NPF, BOPO, FDR, ROA